2015
DOI: 10.1038/nrendo.2015.66
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid hormone transporters—functions and clinical implications

Abstract: The cellular influx and efflux of thyroid hormones are facilitated by transmembrane protein transporters. Of these transporters, monocarboxylate transporter 8 (MCT8) is the only one specific for the transport of thyroid hormones and some of their derivatives. Mutations in SLC16A2, the gene that encodes MCT8, lead to an X-linked syndrome with severe neurological impairment and altered concentrations of thyroid hormones. Histopathological analysis of brain tissue from patients who have impaired MCT8 function ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(180 citation statements)
references
References 113 publications
1
172
0
7
Order By: Relevance
“…Previous studies on adult Mct8-knockout mice showed that T3 levels were elevated not only in the liver but also in the kidney (15,16). In agreement with the findings observed in mice treated chronically with T3, TRb expression was significantly decreased in the liver but not in the kidney in Mct8-knockout mice (Fig.…”
Section: Adaptations During Hyperthyroidism and Withdrawal 855supporting
confidence: 80%
“…Previous studies on adult Mct8-knockout mice showed that T3 levels were elevated not only in the liver but also in the kidney (15,16). In agreement with the findings observed in mice treated chronically with T3, TRb expression was significantly decreased in the liver but not in the kidney in Mct8-knockout mice (Fig.…”
Section: Adaptations During Hyperthyroidism and Withdrawal 855supporting
confidence: 80%
“…The other transporters are also capable of transporting additional substances including steroids and amino acids (Bernal et al 2015). Studies on transgenic mouse models and observations in patients with pathogenic mutations in TH transporters indicate that MCT8, MCT10 and OATP1C1 are the main transporters of (patho)physiological importance to TH transport in vivo (Bernal et al 2015, Visser 2016). MCT8 preferentially transports T 4 , whereas MCT10 preferentially transports T 3 (Visser 2016).…”
Section: Intracellular Thyroid Hormone Metabolismmentioning
confidence: 99%
“…MCT8 preferentially transports T 4 , whereas MCT10 preferentially transports T 3 (Visser 2016). OATP1C1 transports T 3 , T 4 and rT 3 with high specificity; however, it has the lowest affinity for T 4 out of these transporters (Pizzagalli et al 2002, Bernal et al 2015, Visser 2016. Transporter expression is cell type-specific and differences in distribution have been observed between humans and rodents (Bernal et al 2015).…”
Section: Intracellular Thyroid Hormone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 and type 2 5ʹ-deiodinases (DIO1 and DIO2) convert T 4 into active T 3 , and type 3 5ʹ-deiodinase (DIO3) inactivates T 4 and T 3 to form reverse T 3 and T 2 , respectively (Arrojo et al 2013, Charalambous & Hernandez 2013, Gereben et al 2008. Actions of deiodinases and transporters are crucial for normal maintenance of both intracellular and circulating TH levels, as well as function of HPT axis (Bernal et al 2015, Fonseca et al 2013, Hernandez et al 2007, Heuer & Visser 2013, Hoftijzer et al 2011, Schweizer & Kohrle 2013. Physiological effects of TH are largely mediated by regulation of gene transcription by TH receptors (TRs): ligand-dependent transcription factors that belong to the nuclear receptor (NR) superfamily.…”
Section: Introductionmentioning
confidence: 99%